Criteria for individualization of punishment under the criminal law USSR - Irina Nailjevna Ainoutdinova, Karina Arturovna Ainoutdinova, (Opción, 2019)
The purpose of this study is to analyze and clarify the conceptual apparatus, identify and compare norms in the criminal legislation of Russia and some post-Soviet republics on regulation of individualization of punishment and its criteria via theoretical, doctrinal, socio-legal and comparative approaches. As a result, significant similarities in the related regulation are traced in Criminal Codes of a number of post-Soviet states. In conclusion, globalization, internationalization and diversification of crime and its environment only actualize the processes, causing governments, legislators and law enforcers to search for new ways to effectively and fairly impose penalties.